Rezagos en el nivel de autonomía de las mujeres rurales mexicanas en la primera década del siglo XXI - López Guerra, Verónica; Rojas, Olga Lorena (El Colegio de México A.C., 2017)
Considering the progress made in the status of Mexican women in addition to the transformation of Mexican countryside in recent decades, we analyzed the level of autonomy of rural women comparing to their urban counterparts considering some sociodemographic characteristics. We use data from the National Survey on the Dynamics of Household Relationships (ENDIREH) 2011. Our findings suggest that rural women still lag behind urban women, although there are some nuances if we consider some sociodemographic variables.